51 VITAMIN D DEFICIENCY IS ASSOCIATED WITH INCREASED RISK OF ATRIAL FIBRILLATION: A CROSS-SECTIONAL ANALYSIS. (25th October 2022) - Kavanagh, M; Bradley, E; Hoey, L; Hughes, C; McNulty, H; Ward, M; Strain, JJ; Tracey, F; Molloy, A; Laird, E; Cunningham, C; McCarroll, K
Abstract: Background: Atrial Fibrillation (AF) is prevalent (up to 10.9%) in Irish adults aged over 65 and significantly increases stroke risk, as well as being associated with greater stroke severity. Identifying potential contributing factors to development of AF offers opportunity for AF prevention and reduction in associated morbidity. Low vitamin D status has been associated with AF but studies are inconsistent. We aimed to assess the potential relationship between vitamin D deficiency and self-reported AF in older Irish adults. Methods: Participants were from a large cross-sectional study of Irish adults aged >60 years, recruited from hospital outpatient services and GP practises. The diagnosis of AF was based on self-report so those with a Mini Mental State Examination (MMSE) <25 were excluded. Vitamin D deficiency was defined as a 25(OH)D <30 nmol/l. The relationship between deficiency and AF was explored in regression models. Results: 4264 participants, mean age 73.1± 8.0 years, female (67.4%) and 11.9% had AF. There was a higher prevalence of AF in those who were deficient vs non-deficient (17.2% vs 10.9%, P<0.0001). In a subsample (n = 4043), increased risk remained after adjusting for age, gender, season, vitamin D supplement use, body mass index, timed up and go, alcohol intake, smoking status, hypertension, diabetes, and heart disease (coronary artery disease and/or heart failure) (OR: 1.3, 1.1- 1.7, P =0.023). Conclusion: We identified that vitamin D deficiency was independently associated with a 30% increased likelihood of self-reported AF in older adults. Vitamin D is known to inhibit the renin angiotensin, aldosterone system which may play a role in both structural and electrical remodelling of the atrium. It may also have anti-inflammatory properties which could protect against AF. We were not able to distinguish between valvular and non-valvular AF though findings offer an interesting insight for potential further investigation.